Gender Differences in the Relationships between Research Impact and Compensation and Promotion: A Case Study Among PhD/PharmD Medical/Dental School Faculty - McGee, Andrew; Lacy, Paige; Oswald, Anna; Rosychuk, Rhonda J. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
We examine whether the effects of research impact on faculty compensation and promotion to full professor differ for male and female associate and full professors in the Faculty of Medicine & Dentistry at the University of Alberta. We exclude faculty with MDs and DDSs and proxy for research impact using the faculty member’s h-index, where h represents the number of publications that have been cited at least h times. We find that while the compensation of male faculty members increases by 0.6% for every one-unit increase in the h-index, the compensation of female faculty is essentially uncorrelated with their h-indices. We likewise find that for female faculty to be promoted to full professor they have to have higher research impact proxies than their male peers. Our findings highlight the urgent need for more research on the gendered relationships between research impact and career rewards among faculty.